Peran Uji Kompetensi Wartawan dalam Menjaga Mutu Jurnalisme di Kalimantan Barat - Suwandi, Wawan (Jurnal Dinamika Ilmu Komunikasi, 2025)
In the midst of a growing crisis of public trust in journalism triggered by digital disruption and the proliferation of disinformation professionalization has emerged as a crucial strategy for restoring the authority and quality of the profession. This article aims to analyze the role and effectiveness of the Journalist Competency Test (UKW) as implemented by the regional professional organization, the Indonesian Journalists Association (PWI) of West Kalimantan, in maintaining journalistic quality. Using a qualitative case study approach and thematic analysis of event documents, news reports, training materials, and regulatory frameworks, the study examines how national standards are operationalized at the local level. The findings reveal that the UKW functions as a vital formal mechanism for standardizing basic journalistic competencies and receives strong support from various stakeholders, including local government. However, the study also identifies a significant gap between certified competencies and everyday journalistic practices. The main challenges include the persistent culture of “press release journalism” and potential ethical tensions arising from close collaboration between professional organizations and government institutions. The study concludes that while the UKW is necessary, it remains insufficient to ensure journalistic quality in a holistic manner. Professional organizations must complement this formal testing mechanism with continuous mentoring and training programs that emphasize critical inquiry and ethical independence to truly elevate the integrity of the journalistic profession.